Adipogenesis, Osteogenesis, and Chondrogenesis of Human Mesenchymal Stem/Stromal Cells: A Comparative Transcriptome Approach - Robert, Anny W.; Marcon, Bruna H.; Dallagiovanna, Bruno; Shigunov, Patrícia (Frontiers in Cell and Developmental Biology, 2020)
Adipogenesis, osteogenesis and chondrogenesis of human mesenchymal stem/stromal cells (MSC) are complex and highly regulated processes. Over the years, several studies have focused on understanding the mechanisms involved in the MSC commitment to the osteogenic, adipogenic and/or chondrogenic phenotypes. High-throughput methodologies have been used to investigate the gene expression profile during differentiation. Association of data analysis of mRNAs, microRNAs, circular RNAs and long non-coding RNAs, obtained at different time points over these processes, are important to depict the complexity of differentiation. This review will discuss the results that were highlighted in transcriptome analyses of MSC undergoing adipogenic, osteogenic and chondrogenic differentiation. The focus is to shed light on key molecules, main signaling pathways and biological processes related to different time points of adipogenesis, osteogenesis and chondrogenesis.